A Study on Various Packet Classification Algorithm for Network Security Systems - Pandey, Chanchal; Verma, Dipti (International Journal of Computer Sciences and Engineering, 2018)
Routers can likewise function as firewalls and perform variety of operations on the incoming and outgoing packets. On the off chance that when every one of the packets share common header attributes, it is named as a packet flow. With a specific end goal to classify a packet, routers perform a query on a classifier table utilizing at least one fields from the packet header to classify the packet into its relating flow. A classifier is a set of rules which distinguish each flow and the fitting actions to be taken for any packet having belonging to that flow. The paper analyzes the problem of packet classification and different proposed systems for the same.